Design and application of an arterial line set fixation device - WANG, Chenlin; SUN, Xiumei; LI, Xianwen (Chinese Journal of Integrative Nursing, 2024)
Continuous monitoring of invasive blood pressure can provide real-time, accurate data monitoring for ICU patients and provide effective guidance for emergency rescue and following treatment, so flexible fixation devices are essential to ensure the accuracy of patient arterial blood pressure measurement. This study introduces the design and application of a utility model arterial line set fixation device, which can effectively improve the flexibility of arterial line fixation and increase the comfort of patients. (有创血压的持续监测可以为ICU患者提供实时、准确的数据监测, 为临床救治提供有效的指导。灵活的固定装置对于确保患者动脉血压测量的准确性至关重要。本文介绍一种实用新型动脉插件固定装置的设计和使用方法, 旨在有效提高动脉插件固定的灵活性, 实现固定高度和角度可调功能, 增加了患者的舒适性。)